2019
DOI: 10.3390/ijerph17010130
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Mortality-to-Incidence Ratios and Health Care Disparities in Testicular Cancer

Abstract: The mortality-to-incidence ratio (MIR) is associated with the clinical outcomes of different types of cancer as well as the ranking of health care systems. However, the association between MIRs for testicular cancer and health care disparities, including differences in expenditures and health system rankings, has not yet been reported. We used the Spearman’s rank correlation coefficient (CC) to analyze the correlation between testicular cancer MIRs and both total expenditures on health/gross domestic product (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Our previous study showed that a favorable MIR for testicular cancer was associated with higher total expenditure on health/GDP [19]. The results response to a previous study which also revealed a strong inverse relationship between HDI and MIR for testicular cancer [29].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Our previous study showed that a favorable MIR for testicular cancer was associated with higher total expenditure on health/GDP [19]. The results response to a previous study which also revealed a strong inverse relationship between HDI and MIR for testicular cancer [29].…”
Section: Discussionsupporting
confidence: 58%
“…Among the epidemiological models, mortality-to-incidence ratio (MIR) is a feasible method to illustrate the global trends although it cannot replace the role of a cohort survey [12][13][14][15][16][17][18]. Our previous study showed that a favorable MIR for testicular cancer was associated with a better World Health Organization ranking and a higher total expenditure on health/GDP [19]. However, updated data enabled an analysis of MIR trends and an investigation of the association between the disparities of countries and the improvement in MIR.…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increasing number of men diagnosed with cancer, especially testicular cancer, which can trigger infertility, impact their quality of life and cause prolonged toxicity due to drugs employed in the treatment (Chen et al, 2019;Punab et al, 2017). However, it has been shown that this type of cancer is one of the most curable malignancies, which reinforces the need for studies to understand the progression of the disease in search for early therapy (Adra and Einhorn, 2017;Howlader et al, 2019;Smith et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Mortalityto-incidence ratios (MIR) have been used for more than 40 years, first as a measure of completeness of cancer registries (13,14). Where quality of data is good, MIR can be a valid proxy indicator for survival estimates (calculated as 1-MIR) (14)(15)(16), and has already been used in multiple cancer types (17)(18)(19)(20)(21), including melanoma (22)(23)(24). Despite this, the use of MIR for survival estimation is mathematically questionable as the calculation does not use the same population for incidence and mortality (13).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on various types of cancer in OECD countries also discussed the potential of MIR as a measure for evaluation the success of cancer surveillance and screening (16,17,26). Studies generally found reverse correlation between healthrelated expenditure and MIR or development and MIR in multiple cancer types (18,20,23). The GLOBOCAN database of the International Agency for Research on Cancer (IARC) contains the best available evidence on age-standardized cancerspecific incidence and mortality.…”
Section: Introductionmentioning
confidence: 99%